Developing a reflective practice model for engineering leadership. Issue 2 (3rd March 2016) - Finlayson, Alexander
Abstract: This paper advances discourse pertaining to the development of a reflective practice model in engineering leadership. It is based on reflective experiences over a four-year period that were developed as part of a Doctoral in Business Administration module. It is contextualised within an engineering consultancy and the narrative is described from an Engineering Leadership perspective; the narrative is also woven with theory and there is the inclusion of a DBA Practitioner lens on the findings. The paper identifies the model developed for reflective practice and presents evidence of personal learning and thinking styles as its outcome. The paper concludes that reflective practice is a personal journey of learning and that model development is a choice of what suits the individual.